Fungsi Pemerintah Desa dalam Pengelolaan Pasar Desa untuk Meningkatkan Pendapatan Asli Desa di Desa Helanlangowuyo Kecamatan Ile Boleng Kabupaten Flores Timur - Aloysius Kewa Ama; Rafael Rape Tupen; Marlyani Anita Seran (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
The Village Government has a very important function in managing all resources in the Village, one of which is the potential of the village market. The Village Market is a market built and managed by the Village Government with a place of business in the form of shops, stalls and tents or other similar names. Especially the Helanlangowuyo Village Government which is provided for traders. Based on Helanlangowuyo Village Regulation Number 6 of 2016 concerning Helanlangowuyo Village Finance Article 8 concerning the amount of village market retribution. The formulation of the problem in this study: (1) How is the Function of the Village Government in managing the Senadan Village Market to increase the original village income in Helanlangowuyo Village? (2) How does the contribution of the Senadan Village Market retribution to the original village income in Helanlangowuyo Village? (3) What are the inhibiting factors of the Village Government's Function in managing the Senadan Village Market to increase PADes in Helanlangowuyo Village? This type of research is empirical legal research which is a study of legal identification and legal effectiveness so that in its preparation, field research is carried out that utilizes data supported by primary data sources and secondary data. The results of the research and discussion show that: (1) In the management of the Senadan Village Market, the Helanlangowuyo Village Government faces challenges related to the status of the market land which is still a rental system and market facilities which are still very limited. (2) The contribution of market levies from 2021 to 2023 has decreased significantly, with the total contribution decreasing from IDR 3,275,250 in 2021 to IDR 3,027,750 in 2023. (3) The management of the Senadan Village Market faces obstacles in the form of a lack of clear regulations, low quality of human resources, lack of public awareness and inadequate conditions of facilities and infrastructure.